2005
DOI: 10.1038/sj.cdd.4401604
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 phosphorylates and upregulates Akt/PKB

Abstract: Treatment of Jurkat cells with specific inhibitors of protein kinase CK2 induces apoptosis. Here we provide evidence that the antiapoptotic effect of CK2 can be at least partially mediated by upregulation of the Akt/PKB pathway. Such a conclusion is based on the following observations: (1) inhibition of CK2 by cell treatment with two structurally unrelated CK2 inhibitors induces downregulation of Akt/PKB, as judged from decreased phosphorylation of its physiological targets, and immunoprecipitate kinase assay;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
283
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 310 publications
(311 citation statements)
references
References 39 publications
15
283
1
1
Order By: Relevance
“…Similar results were obtained treating cells with other CK2 inhibitors, either structurally related or not to TBB (not shown). Figure 4 also shows that the phosphorylation degree of two CK2 target sites (Ser129 of Akt, Di Maira et al, 2005 and Thr 117 of BAD, Klumpp et al, 2004), detected by phospho-specific antibodies, is higher in R-CEM than in S-CEM. From all these data, it can be concluded that CK2-catalysed protein phosphorylation is much more pronounced in R-CEM cells, consistent with their higher content in CK2a.…”
Section: Ck2 Activity In R-cem and S-cemmentioning
confidence: 90%
See 3 more Smart Citations
“…Similar results were obtained treating cells with other CK2 inhibitors, either structurally related or not to TBB (not shown). Figure 4 also shows that the phosphorylation degree of two CK2 target sites (Ser129 of Akt, Di Maira et al, 2005 and Thr 117 of BAD, Klumpp et al, 2004), detected by phospho-specific antibodies, is higher in R-CEM than in S-CEM. From all these data, it can be concluded that CK2-catalysed protein phosphorylation is much more pronounced in R-CEM cells, consistent with their higher content in CK2a.…”
Section: Ck2 Activity In R-cem and S-cemmentioning
confidence: 90%
“…CK2a-subunit antisera were raised in rabbit against the sequence of the human protein at C terminus (376-391), N terminus (2-15), or central region (188-202), CK2a-subunit monoclonal antibodies were from Calbiochem (Darmstadt, Germany) (1AD9), CK2b-subunit antibodies were raised in rabbit against the whole human protein, and also purchased from BD Transduction Laboratories (Erembodegen, Belgium), CK2a 0 -subunit, total Akt, actin, lactate dehydrogenase, and lamin B antibodies were from Santa Cruz Biotechnology (Santa Cruz, CA, USA), PARP antibodies were from Roche (Basel, Switzerland), Akt Sp129 phospho-specific antibodies were raised in rabbit as described elsewhere (Di Maira et al, 2005), BAD antibodies were from Cell Signaling Technology (Danvers, MA, USA), BAD Tp117 phosphospecific antibodies were kindly provided by Dr Klumpp (Munster, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 A number of studies have shown that CK2 phosphorylates PTEN in the C-terminal region, stabilizes the protein against ubiquitin-mediated proteasomal degradation and regulates PTEN activity in a negative manner. 26 --28 In addition to its direct regulation of PTEN, CK2 is able to activate AKT through direct phosphorylation 29 and through an indirect mechanism preventing the dephosphorylation of its active form. 30 CK2 regulation of other hematopoietic-specific transcription factors and molecules CK2 has also been described as a regulative kinase of a multitude of hematopoietic transcription factors and molecules.…”
Section: A Possible Role For Ck2 In Hematopoiesis?mentioning
confidence: 99%